Methodological, reporting, and evidence quality of systematic reviews of traditional Chinese medicine for ischemic stroke - Sun, Shouyuan; Zhao, Liang; Zhou, Xiaoli; Liu, Xuewu; Xie, Zongzhi; Ren, Jun; Zhou, Baoyuan; Pan, Yawen (Frontiers in Pharmacology, 2023)
Abstract Objective: To critically appraise whether published systematic reviews/meta-analyses of traditional Chinese medicine (TCM) for adults with ischemic stroke are of sufficient quality, and to rate the quality of evidence using the GRADE approach. Method: A literature search was performed on the Cochrane Library, PubMed, CNKI, and SinoMed databases by March 2022. The inclusion criteria were systematic reviews/meta-analyses of traditional Chinese medicine (TCM) in adults who suffered from ischemic stroke. A Measure Tool to Access Systematic Reviews 2 (AMSTAR-2) and Preferred Reporting Items for Systematic Reviews and Meta-Analyses for Abstract (PRISMA-A) statement were used to assess the methodological and reporting quality of the included reviews. The Grade of Recommendations Assessment, Development and Evaluation (GRADE) system was utilized to assess each report’s evidence level. Results: Of the 1 908 titles and abstracts, 83 reviews met the inclusion criteria. These studies were published between 2005 and 2022. The results of AMSTAR-2 showed that 51.4% of the items were reported, but the registration, reasons for the study designs for inclusion, the list of excluded studies, and information on the funding were ignored in the majority of reviews. The results of PRISMA-A showed that 33.9% of items were reported, and the information on registration, limitation, and funding was not available. The assessment of the evidence with GRADE showed that more than half (52/83) of the included studies had either low or very low levels of evidence. Conclusion: The reporting quality in the abstract of systematic reviews/meta-analyses on TCM for ischemic stroke is poor and does not facilitate timely access to valid information for clinical practitioners. Although the methodological quality is of a medium level, this evidence lacks certainty, especially with a high risk of bias in individual studies.